2019
DOI: 10.1136/bmjgast-2018-000219
|View full text |Cite
|
Sign up to set email alerts
|

Association of fatty liver disease with mortality outcomes in an Eastern Finland male cohort

Abstract: ObjectiveFatty liver disease (FLD) has been associated with extrahepatic morbidity outcomes. However, reports on the association of FLD, assessed using fatty liver index (FLI), with mortality outcomes have been inconsistent. Our objective was to examine the effect of metabolic factors (blood pressure, insulin, fasting glucose, lipoproteins) on the associations of FLI with mortality outcomes among middle-aged men.Study designProspective cohort study.MethodsOur subjects were 1893 men at baseline from 1984 to 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Similar associations with all-cause mortality have been observed in two smaller European prospective studies [36,37]. Another prospective [38]. The study observed that individuals with NAFLD had significantly higher mortality risk than those without NAFLD [38].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Similar associations with all-cause mortality have been observed in two smaller European prospective studies [36,37]. Another prospective [38]. The study observed that individuals with NAFLD had significantly higher mortality risk than those without NAFLD [38].…”
Section: Discussionsupporting
confidence: 74%
“…Another prospective [38]. The study observed that individuals with NAFLD had significantly higher mortality risk than those without NAFLD [38]. A novel aspect of our study is our choice of a second, but arbitrary, cut-off value of FLI ≥ 80, assuming that those with a very high FLI score have more serious degrees of steatosis, needing to be validated in additional studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…FLI is a noninvasive and simple biomarker for diagnosis of NAFLD and is calculated by using BMI, WC and levels of GTP and triglycerides 25) . It has been reported that FLI can predict not only NAFLD but also other metabolicrelated diseases including diabetes mellitus [40][41][42][43] , hypertension [44][45][46][47] and chronic kidney disease [48][49][50][51] . Dysregulation of iron metabolism represents another typical feature of NAFLD associated with more severe hepatic and cardio-metabolic damage 52) .…”
Section: Correlation and Multivariable Regression Analyses For Pcsk7 Levelmentioning
confidence: 99%